Kontrol Diri dan Bimbingan Islam - Muhyi, Syaiful (Tasamuh: Jurnal Studi Islam, 2017)
Anxiety is the first part to feel something. The anxiety is usually called by a situation that gives an affects, nevertheless we cannot know what the influence it is. It is the most of the properties that are not preferred as a real feeling. But this does not mean an overall view of personal traits, and not all circumstances unpopular called anxiety. The anxiety exists when a person cannot predict or control the situation of the object, so that it makes them fear of the object. Clearly explained, anxiety as a condition of inefficacy (incertitude ourselves on the ability) deals with the situation. Responding to the anxiety condition, Islam also has a concept. The rationale regarding the counseling Islam initially starts from the assumption that religion is a pure necessity for mankind. God has created man as the best of creatures and the best of shape. So that only faith in God is the one who would deliver happiness, serenity, tranquility or even anxiety for human being, restlessness. Instead the unbelievers will find and is the root of a problem, and the lack of peaceful for all mankind.